Komodo-7B with Hybrid Retrieval and Q-LoRA for Indonesian Population Administration Question Answering - Anindo Saka Fitri; Abdul Rezha Efrat Najaf; Eko Wahyudi; Adelia Azizatul Haq; Sugiarto Sugiarto; I Gede Susrama Mas Diyasa (DRPM - ITB, 2026)
Fast, responsive, and informative public services are societal demands that must be fulfilled by government agencies, among which the Department of Population and Civil Registration of Surabaya City. To enhance service quality, this study developed a Large Language Model (LLM)-based Question Answering (QA) system to address public inquiries regarding Identity Card (ID) and Family Card (FC) services. The proposed system utilizes the Komodo-7B model, which was customized using Quantized Low-Rank Adaptation (Q-LoRA) fine-tuning and integrated with a Retrieval-Augmented Generation (RAG) approach to improve the accuracy and relevance of the generated responses. The training process leveraged a real-world complaint dataset from Disdukcapil alongside the open-source MS MARCO dataset. Furthermore, the RAG implementation employs sentence vectorization via SentenceTransformer and cosine similarity-based context retrieval. System performance was evaluated using ROUGE and METEOR metrics across four scenarios: Komodo-7B Base, RAG Komodo-7B Base, Fine-Tuned Komodo-7B, and RAG Fine-Tuned Komodo-7B. The results show that the RAG Fine-Tuned Komodo-7B configuration delivered the best performance, achieving F1-Scores of 0.3554 for ROUGE-1, 0.3096 for ROUGE-L, and 0.2886 for METEOR.